Laparoskopna radikalna cistektomija sa ekstrakorporalnom derivacijom urina - početno iskustvo i preliminarni rezultati - Shabani, Bashkim; Ivanovski, Ognen; Gurmeshevski, Slobodan; Pejkov, Risto; Panovska Petrusheva, Aleksandra; Gavrilovska-Brzanov Aleksandra; Petrushevska, Gordana (Okruzna podružnica SLD Leskovac, 2020)
SUMMARY Introduction and objectives: To report our experience with laparoscopic radical cystectomy (LRC) and extracorporeal urinary diversion for muscleinvasive bladder cancer. We have evaluated and summarized the surgical outcomes and complications of this procedure. Patients and methods: We have evaluated retrospectively all patients who underwent LRC at our clinic over a one year period. In all patients, ureteroileocutaneostomy (Bricker technique) was performed for urinary derivation. We have analyzed the following parameters: patient demographic data, laboratory data, intraoperative fluid volume, estimated blood loss and transfusion requirements. Respiratory parameters including arterial blood gas data, anesthesia time, surgical time, time of oral intake, admission to ICU (intensive care unit), hospital stay and any adverse events during the whole period of hospitalization were also analyzed. Results: Patients had similar demographic characteristics. Estimated intraoperative blood loss was 392 ml. Due to prolonged surgical time and CO2 pneumoperitoneum, hypercapnia was observed in 3 patients. Patients had a short period of bowel dysfunction and rapid shift from parenteral to oral nutrition, short hospital stay and low rate of surgical compilations. Conclusion: The results of our study have shown that laparoscopic radical cystectomy is a safe, feasible, and effective alternative to open radical cystectomy. Ex tra cor - po real urinary diversion through a small incision decreases the operating time, while maintaining the benefits of laparoscopic surgery. However, some larger prospective evaluation is to be made for summarizing the overall conclusions.
Laparoscopic radical cystectomy with extra corporeal urinary diversion: initial experience and preliminary results
Keywords: bladder cancer; radical cystectomy; laparoscopy